Balancing intermolecular interactions in the design and synthesis of supermolecules - Schultheiss, Nathan C. (Kansas State University, 2007)
The directed-assembly of small molecular building-blocks into discrete supermolecules or extended networks through non-covalent intermolecular interactions is an on-going challenge in the field of crystal engineering. This synthetic challenge may be overcome by identifying or establishing a hierarchy of intermolecular interactions which, in turn, may facilitate a modular supramolecular assembly process producing final products in high yields. A family of three 3-pyridine/amino-pyrimidine supramolecular reactants (SR’s) was prepared and allowed to react with aromatic carboxylic acids producing nine 1:1 molecular co-crystals and four 1:1 ionic salts through heteromeric O-H···N/N-H···O or charge-assisted N–H+···O-/N–H···O- hydrogen bonds with the amino-pyrimidine binding site. We introduced a Q-value, based on AM1 calculations, to show that the amino-pyrimidine moiety is a superior hydrogen-bond acceptor for an incoming carboxylic acid. The amino-pyrimidine/carboxylic acid synthon resulted 13/13 times (100 % yield) even in the presence of other potentially disruptive intermolecular interactions. However, reacting a 4-pyridine/amino-pyrimidine SR and a carboxylic acid in a 1:2 ratio, resulted in structures containing both acid/amino-pyrimidine and acid/pyridine synthons. The same family of pyridine/amino-pyrimidine SR’s were allowed to react with halogentated benzoic acids in which the amino-pyrimidine/carboxylic acid synthon formed 7/7 times (100 % yield) and halogen bonds (N···I or N···Br) extended the SR/acid dimers into polymeric networks 4/7 times (57 %). These results were rationalized through a hierarchial view of intermolecular interactions consisting of hydrogen and halogen bonds. Four bifunctional 3-pyridine/amino-pyrimidine or amino-pyridine SR’s were reacted with neutral metal complexes producing thirteen crystal structures in which the pyridyl moiety coordinates to the metal center 13/13 times (100 % yield) and amino-pyrimidine···amino-pyrimidine hydrogen bonds link the neighboring metal-ligand complexes 10/13 times (77 % yield) into 1-D or 2-D extended architectures. Finally, we synthesized and characterized a series of tetra-substituted hydrogen bond donor and acceptor functionalized, i.e. pyridyl, amino-pyridine, carboxylic acid, resorcinarene-based cavitands forming deep-walled cavitands through amino-pyridine···carboxylic acid heteromeric synthons and a heterodimeric molecular capsule through pyridyl···carboxylic acid hydrogen bonds. The heterodimeric capsule is only one of three, of its type, characterized crystallographically.
Keywords: Supramolecular Chemistry; Hydrogen bonds; Chemistry, Inorganic (0488); Chemistry, Organic (0490)